2010
DOI: 10.1542/peds.2009-2268
|View full text |Cite
|
Sign up to set email alerts
|

Human Recombinant Erythropoietin in Asphyxia Neonatorum: Pilot Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Neuronal apoptosis that follows hypoxia-ischemia is triggered by upregulation of NO synthase, with excessive accumulation of NO and release of excitatory amino acids such as glutamate. Animal studies demonstrated the ability of erythropoietin to attenuate these mechanisms. WHAT THIS STUDY ADDS:The administration of erythropoietin to infants with asphyxia with mild/moderate HIE was associated with favorable decreases in endogenous NO production, decreases in seizure activity, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
115
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 35 publications
6
115
0
1
Order By: Relevance
“…Nevertheless, we believe that this finding is of importance as rHuEPO has a crucial role in the field of neonatal medicine. In recent years, both animal studies 24,25 and human clinical trials 16,26 have demonstrated that the use of rHuEPO reduces the severity of perinatal asphyxia, thus reducing the risk of disability in neonates. There is evidence to suggest that EPO has a protective effect on the developing kidney, 27 in the treatment of periventricular leukomalacia in neonates, 28 and in the reduction in ventilatory support time in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we believe that this finding is of importance as rHuEPO has a crucial role in the field of neonatal medicine. In recent years, both animal studies 24,25 and human clinical trials 16,26 have demonstrated that the use of rHuEPO reduces the severity of perinatal asphyxia, thus reducing the risk of disability in neonates. There is evidence to suggest that EPO has a protective effect on the developing kidney, 27 in the treatment of periventricular leukomalacia in neonates, 28 and in the reduction in ventilatory support time in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]8 Two small trials in China and Egypt found that Epo therapy improved short-term neurologic outcomes after HIE. 18,19 However, these trials used alternative dosing regimens and did not include the use of hypothermia. In countries where therapeutic hypothermia has become a standard of care, [20][21][22] novel neuroprotective agents should be evaluated together with hypothermia.…”
mentioning
confidence: 99%
“…EPO produced in the central nervous system7 is upregulated after insult and plays a role in neuroprotection 8, 9, 10, 11. Experimental studies have reported that rhEPO possesses neuroprotective properties in different neonatal brain injury animal models,12, 13 and clinical studies have shown that rhEPO treatment reduces brain injury and the incidence of neurological disabilities in infants 8, 14, 15, 16, 17. In addition, improved neurodevelopmental outcomes have been observed in preterm infants with anemia after rhEPO treatment 17, 18, 19, 20.…”
mentioning
confidence: 99%